2013
DOI: 10.1002/jssc.201300750
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional separation of tryptic peptides from human serum proteins using reversed-phase, strong cation exchange, weak anion exchange, and fused-core fluorinated stationary phases

Abstract: Proteome profiling of crude serum is a challenging task due to the wide dynamic range of protein concentrations and the presence of high-abundance proteins, which cover >90% of the total protein mass in serum. Peptide fractionation on strong cation exchange, weak anion exchange in the electrostatic repulsion hydrophilic interaction chromatography (ERLIC) mode, RP C18 at pH 2.5 (low pH), fused-core fluorinated at pH 2.5, and RP C18 at pH 9.7 (high pH) stationary phases resulted in two to three times more identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(23 citation statements)
references
References 41 publications
1
22
0
Order By: Relevance
“…ERLIC has been reported to separate phosphopeptides relatively evenly across fractions, permitting higher numbers of phosphopeptide identifications (34,35). Consistent with these studies, we observed that phosphopeptides separated quite evenly across the 24 ERLIC fractions (Fig.…”
Section: V600esupporting
confidence: 89%
“…ERLIC has been reported to separate phosphopeptides relatively evenly across fractions, permitting higher numbers of phosphopeptide identifications (34,35). Consistent with these studies, we observed that phosphopeptides separated quite evenly across the 24 ERLIC fractions (Fig.…”
Section: V600esupporting
confidence: 89%
“…Boichenko et al [43] reported multidimensional separation of tryptic peptides from human serum proteins. The study demonstrated that peptide fractionation on SCX, weak anion exchange (WAX) in the electrostatic repulsion hydrophilic interaction chromatography (ERLIC) mode, RP C18 at pH 2.5 (low pH), fused-core fluorinated at pH 2.5, and RP C18 at pH 9.7 (high pH) stationary phases resulted in two to three times more identified proteins and three to four times more identified peptides in comparison with 1D nano Chip-LC–MS/MS quadrupole TOF analysis.…”
Section: Methodologies Used To Reduce the Complexity Of Proteomic Smentioning
confidence: 99%
“…20 The second dimension involved a nanoChip-LC (RP C18, pH 2.6) and Q TOF-MS/MS. The highest number of peptides was identified by ERLIC, while an equal number of proteins were identified by ERLIC and high-pH RPLC.…”
Section: De Jong Et Al Compared Erlic-ms Directly With Rplc-ms For Smentioning
confidence: 99%
“…With this combination there is a uniform distribution of peptides among the collected fractions, with peptides eluting in order of decreasing isoelectric point and increasing hydrophilicity. [18][19][20] This order of elution is comparable in some respects to that of isoelectric focusing but is accomplished without ampholines or a complex mixture of buffering salts. The separation of peptides based on isoelectric point has been exploited for the study of protein/ peptide deamidation 21,22 as the original residue, Asn, and its deamidated products n-Asp and isoAsp have different pKa values.…”
mentioning
confidence: 99%